Le cadrage dans les technographismes, cas des mèmes internet. Vers une analyse socio-sémiotique - Khadidja Rahmani; Salim Khider (Multilinguales)
This study is part of social semiotic field founded by Theo Van Leeuwen. Through a qualitative analysis we seek first to define, the different types of framing in Internet memes, then to verify the impact of framing using on the visibility and the readability of these composites and finally to deduce the nature of the relation text-image in this type of technographisms.